Colonic surgery in emergency - Barquet, Alberto; Kamaid, Emil (Cirugía del Uruguay, 2021)
The paper contains general considerations on the therapeutical conduct to be followed in emergency colon surgery: on the use, in unplanned surgery, of different techniques accoding to the type of lesion and its complications; and on the need of colonic resection in order to erradicate the disease. Other points refer to the immediate procedure employed on the resulting tips in a colon the contents whereof have not been prepared as in elective operations and to the different procedures employed according to the different schools. Then the paper presents five cases of different lesions of the colon where resection and primary anastomosis without a safety a us was performed and which had a good evolution in all cases. A detailed account of the technique employed is given: selection and preparation of the tips, after decompression and evacuation of the contents and terminal and monoplane anastomosis we believe this method is better because the mucose is not incorporated; control of anastomosis; through washing of the peritoneum; progression of Cantor's probe to the jejunum; closing of the wall with retention suture. This is followed by comments supporting new radical methods, which contemporary medicine has made possible. Comparison of statistics on staged and singlestage operations indicate that a revaluation of these advanced methods-which are less revolutionary than they appear to be becomes necessary. Stress is laid on the fact that it is not possible to establish the basis of emergency colonic surgery and that in selecting the procedure · to be followed the surgeon should be guided by operatory findings and the state of the patient.